Development of interactive e-content to enhance listening skill and language comprehension among secondary school students - Nitha Varghese; Kennedy Andrew Thomas (International Journal of Evaluation and Research in Education (IJERE), 2026)
The present study aimed to develop interactive e-content, conduct expert validation, and examine the appropriate level. The researchers used a purposive sampling technique to select the sample of 100 secondary school students and 35 teachers from the Kerala state scheme. The researchers adopted the analysis, design, development, implementation, and evaluation (ADDIE) model to develop interactive e-content. The study employed two quantitative methods. Firstly, the study administered expert validation sheets to three content and two media experts to validate developed interactive e-content. The study utilized the percentage analysis to evaluate the results of the expert validation sheets. Secondly, the study administered a survey questionnaire to 100 secondary school students and 35 teachers to examine the appropriate level of interactive e-content. The study employed the correlation method to analyze the questionnaire results, examining the strength and direction of relationships between variables. The average score of content expert validation is 95.5% and media expert validation is 91.5% confirm that the developed interactive e-content is highly valid and appropriate. A major challenge for the researchers was the insufficient internet speed in rural areas of Kerala. The study recommends that teachers have to develop interactive multimedia teaching-learning aids to improve listening, speaking, reading, and writing (LSRW) among students.